12
$\begingroup$

solve the differential equation.

$$\frac{xdx+ydy}{xdy-ydx}=\sqrt{\frac{a^2-x^2-y^2}{x^2+y^2}}$$

The question is from IIT entrance exam paper. I have tried substituting $x^2=t\ and \ y^2=u$ but was not a worth try.

Thanks in advance.

$\endgroup$
3
  • 1
    $\begingroup$ This post is visible from outer space$\ldots$ $\endgroup$
    – Lucian
    Nov 10 '14 at 14:04
  • 1
    $\begingroup$ It looks like the imaginary part of (x+iy)(dy-idx) which is just z and -idz multiplied together in the numerator and the real part of that same expression in the denominator along with (x+iy)(x+iy)* in the radical. $\endgroup$
    – Kainui
    Nov 10 '14 at 15:43
  • $\begingroup$ $sin^{-1}(\frac{\sqrt{x^2+y^2}}{a})=tan^{-1}(\frac{y}{x})+c$ @Kainui solution $\endgroup$
    – gaufler
    Nov 10 '14 at 16:05
16
$\begingroup$

This question is a bit of a nightmare for an entrance exam. Anyway, first observe that $$d(x^2 + y^2) = 2xdx + 2ydy$$ This suggests that using a variable $u = x^2 + y^2$ is useful, as we also have the RHS (right hand side)

$$RHS = \sqrt{\frac{a^2 - u}{u}}$$

The denominator on the LHS (left hand side) is slightly tricker; the minus sign suggests a derivative of $1/x$. Let's try $v = y/x$, then $$dv = \frac{1}{x} dy - \frac{y}{x^2} dx$$

Hence $x^2 dv = xdy - ydx$ and we can write the LHS

$$LHS = \frac{x dx + y dy}{x dy - y dx} = \frac{1}{2x^2} \frac{du}{dv}$$

If we can write the $x^2$ terms of $u$ and $v$ we will have an ODE in just those variables: $$ \frac{1}{v^2 + 1} = \frac{x^2}{x^2 + y^2} = \frac{x^2}{u} \ \ \hbox{ hence } \ x^2 = \frac{u}{v^2 + 1}$$ Thus we can write

$$LHS = \frac{v^2 + 1}{2u} \frac{du}{dv} = RHS = \sqrt{\frac{a^2 - u}{u}}$$

or

$$\frac{du}{dv} = 2\sqrt{u(a^2 - u)} . \frac{1}{v^2 + 1}$$

This equation is separable

$$\int \frac{du}{\sqrt{u(a^2 - u)}} = 2\int \frac{dv}{v^2 + 1}$$

...after a bit of work,

$$\arctan\left( \frac{\sqrt{u}}{\sqrt{a^2 - u}} \right) = \arctan v + C$$

or back in the original variables:

$$\arctan\left( \frac{\sqrt{x^2 + y^2}}{\sqrt{a^2 - x^2 - y^2}} \right) = \arctan\left(\frac{y}{x} \right) + C$$

$\endgroup$
6
  • $\begingroup$ how come the answer be $sin^{-1}(\frac{\sqrt{x^2+y^2}}{a})=tan^{-1}(\frac{y}{x})+c$ $\endgroup$
    – gaufler
    Nov 10 '14 at 16:23
  • 1
    $\begingroup$ These answers are equivalent. Draw a right triangle with hypotenuse $a$ and one side $\sqrt{x^2 + y^2}$. Then the other side is $\sqrt{a^2 - x^2 - y^2}$ and you can see that $$\arcsin\left(\frac{\sqrt{x^2 + y^2}}{a}\right) = \arctan\sqrt{\frac{a^2 - x^2 -y^2}{x^2 + y^2}}$$ $\endgroup$
    – Simon S
    Nov 10 '14 at 16:29
  • 1
    $\begingroup$ ...and thanks for torturing us (me) by not giving us the answer up front! $\endgroup$
    – Simon S
    Nov 10 '14 at 16:30
  • $\begingroup$ Sorry for the turmoil, I rather got this answer later, else I would have posted it earlier itself. $\endgroup$
    – gaufler
    Nov 10 '14 at 16:37
  • $\begingroup$ In my argument above $\arcsin(stuff) = \arctan(other stuff)$ above, I've written the reciprocal of $otherstuff$. $\endgroup$
    – Simon S
    Nov 10 '14 at 22:57
6
$\begingroup$

This equation could have been solved easily in polar coordinates.

\begin{align} x &= z \cos{s} \\ y &= z \sin{s} \end{align} Then \begin{align} dx = \cos(s) \, dz - z\,\sin(s)\, ds \\ dy = \sin(s) \, dz + z\,\cos(s)\, ds \end{align} as well as $$x^2+y^2 = z^2\big(\cos^2(s) + \sin^2(s)\big) = z^2$$ which means that $$z = \sqrt{x^2 + y^2}$$ Now \begin{align} y\,dx = z \sin(s) \cos(s) \, dz - z^2\,\sin^2(s)\, ds \\ x\,dy = z \cos(s) \sin(s) \, dz + z^2\,\cos^2(s)\, ds \end{align} which leads to the difference \begin{align} x\,dy - y\,dx &= z \cos(s) \sin(s) \, dz + z^2\,\cos^2(s)\, ds\\ & - z \sin(s) \cosh(s) \, dz + z^2\,\sinh^2(s)\, ds \\ &= z^2\,\cos^2(s)\, ds + z^2\,\sin^2(s)\, ds \\ &= z^2\big(\cos^2(s) + \sin^2(s)\big) \, ds\\ &= z^2\, ds \end{align} Moreover, \begin{align} x\,dx + y\,dy &= \frac{1}{2}d \left(x^2+y^2\right)\\ &= \frac{1}{2} d(z^2)\\ &= z\,dz \end{align} Consequently \begin{align}\frac{x\,dx + y\,dy}{ x\,dy - y\,dx } &= \frac{z\, dz}{z^2 \, ds}\\ &= \frac{1}{z} \frac{dz}{ds}\end{align} and finaly the equations becomes \begin{align} \frac{1}{z} \frac{dz}{ds} = \frac{x\,dx + y\,dy}{ x\,dy - y\,dx } = \sqrt{\frac{a^2 - x^2 - y^2}{x^2+y^2}} = \sqrt{\frac{a^2 - z^2}{z^2}} = \frac{\sqrt{a^2-z^2}}{z} \end{align} multiply both sides by $z$ and obtain the simple differential equation $$ \frac{dz}{ds} = \sqrt{a^2-z^2}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.